A cytoplasmic factor, calpastatin and ATP together reverse run-down of Ca(2+) channel activity in guinea-pig heart - Hao, Li-Ying (Blackwell Science Inc, 1999)
1. The cytoplasmic extract of bovine heart was separated into four fractions by gel filtration: H (molecular mass > 300 kDa), P (250-300 kDa), L(1) (180-250 kDa) and L(2) (< 180 kDa). The effects of these fractions on the run-down of L-type Ca(2+) channel activity were investigated in guinea-pig ventricular myocytes. 2. After run-down induced by inside-out patch formation, Ca(2+) channel activity was restored by P or H (+ 3 mM ATP) to 7·5 and 5·8 % of that in the cell-attached mode, respectively, but to as high as 86 % by P + H + ATP. 3. The reversal of run-down brought about by the P fraction was mimicked by calpastatin. 4. The restorative effect of calpastatin + ATP showed a biphasic time course: 38 % in the early transient phase and 11 % in the late phase. However, calpastatin + H + ATP showed a sustained effect: 66 % in the early transient phase, and 87 % in the late phase. 5. The effective component of the H fraction showed a protein-like nature: heat and trypsin sensitivity. 6. The activities of cAMP-dependent protein kinase, casein kinase I, casein kinase II, protein tyrosine kinase, protein serine/threonine or tyrosine phosphatases were measured. However, these kinases and phosphatases were not confirmed as the effective component of cytoplasm or the H fraction. 7. Run-down was not prevented by 2 μM phalloidin or 2 μM paclitexal, suggesting that neither actin filaments nor microtubules are directly involved in the run-down. 8. Our results support the view that the basal activity of the Ca(2+) channel is maintained by at least three factors: a protein-like factor in the H fraction, calpastatin, and ATP.